Analysis of Enabling and Inhibiting of Cloud Storage Restriction Policy Implementation in Higher Education: A Systematic Literature Review - Abdul Malik Karim; Feby Artwodini Muqtadiroh (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This study examines enabling and inhibiting factors affecting the implementation of cloud storage restriction policies (e.g., quotas, retention/archiving, data classification, and exceptions) in higher education institutions. A PRISMA-guided systematic literature review was conducted using Scopus and complementary manual searches in Google Scholar, covering English-language publications from the last ten years. Following de-duplication and staged screening, 30 studies were included for synthesis. Findings were analyzed using the Socio-Technical Systems (STS) framework and mapped across People, Structure, Technology, and Process dimensions to capture the interplay between policy design, implementation practices, and technical enforcement. Results indicate that implementation success is driven by human readiness and governance capacity, especially continuous training and mentoring, clear communication, and leadership support that helps balance cost control with user acceptance and compliance. Technological enablers include adequate infrastructure, platform/service integration, and strong access control and information security mechanisms to ensure consistent enforcement. Key barriers include limited digital and data literacy, resistance to change and concerns about data deletion, uneven IT capacity across units, weak SOPs, siloed coordination, complex bureaucracy, vendor dependence, and budget constraints. The study recommends a holistic approach combining strengthened governance, standardized processes, targeted technology investment, and structured change management.